STUDI PENDAHULUAN KENDALI SLIDING MODE - Husain, M.Faisal
Abstract : Variable structure system with sliding mode is a technique originally conceived for continuous systems that is remarkably good in rejecting certain disturbances and parameter variations. Direct digital implementation of the technique suffers from severe limitations, so the design scheme has been developed that specifically address the issues relevant to digital control. This thesis deal with variable structure system with sliding mode in discrete-time frame work. The research effort started to choose a control law that guarantee the state does not leave the boundary layer, or in other word, that was to guarantee the attractive and the invariance property of the boundary layer. In addition, it is shown that the tracking error dynamics inside the boundary layer can be matched with any dynamics having the state feedback form under eigenvalue constraint. To create more sophisticatic tools, the research included investigation in the use of the LQR technique in the design of a sliding surface. The thesis ended by verified the whole concepts in two plant. Simulation result showed good performance in both of the plant.